Determining Factors of Continuance Intention to Use QR Code Mobile Payment on Urban Millennials in Indonesia Empirical Study on Mobile Payment Funds - Shella Azizah; B.P.Kusumo Bintoro; Regina Dinda Octavyra; Achmad Rachmat S (ADI Publisher, 2022)
In this era where technological advances continue to open up business opportunities that allow new entrants with disruptive business strategies to be able to compete with established market leaders. This encourages companies to adopt new technologies, new ways of working to stay relevant in the digital age. This study aims to analyze the determinants of continuance intention to use QR Code Mobile Payment DANA on Urban Millennials in Indonesia which will provide formulation of recommendations for related industries based on the study results of this research. By using quantitative methods, which are used to measure variables in a subject. Through 6 stages in conducting research, which begins with problem formulation followed by preliminary studies, data collection, data analysis in which using the SEM method with PLS (Partial Least Square) followed by discussion and ends with conclusions and suggestions. After conducting a questionnaire assisted by special software that utilizes the PLS (partial Least Square) method, and the results obtained, DANA's QR Code Mobile Payment users will be interested in using it continuously if they already have trust, fun flow in use, and satisfaction. To achieve high trust from users, it takes a quality system and good service quality and understands user needs. DANA Mobile Payment QR Code users feel the flow of pleasure when transacting using the QR Code. Customer satisfaction can be increased by increasing the quality of information or output. Such as increasing the utility of customer service, or even replacing human customer service with AI-based customer service.